Reference intervals for serum sphingosine-1-phosphate in the population-based Study of Health in Pomerania - Moritz, Eileen; Wegner, Danilo; Groß, Stefan; Bahls, Martin; Dörr, Marcus; Felix, Stephan B.; Ittermann, Till; Oswald, Stefan; Nauck, Matthias; Friedrich, Nele; Böger, Rainer H.; Daum, Günter; et al. (Clinica chimica acta, 2017)
The bioactive signaling lipid sphingosine-1-phosphate (S1P) is a potential biomarker for cardiovascular disease (CVD). To date, no reference intervals for S1P have been defined. This study aims to establish a reference range for serum S1P in healthy individuals. We determined reference intervals for S1P levels according to gender and age in a sample of 1339 healthy participants of the Study of Health in Pomerania (SHIP)-TREND cohort after exclusion of subjects with CVD, diabetes mellitus, hypertension, metabolic syndrome, elevated liver enzymes, chronic kidney disease stadium III or IV, or body mass index (BMI)>30kg/m2. Serum S1P was measured by liquid chromatography-tandem mass spectrometry. The median age of the participants was 41 (25th; 75th percentile 32; 51) years, 65% were women. The median serum concentration of S1P was 0.804 (0.694; 0.920) μmol/L. No association with gender and age was observed. The overall reference interval was 0.534–1.242μmol/L (2.5th; 97.5th percentile). Further exclusion of smokers, individuals with BMI>25kg/m2 or elevated lipid levels did not significantly affect median S1P concentrations. This study provides reference intervals for serum S1P in healthy individuals. Total serum S1P concentrations vary irrespectively of age, gender, BMI or smoking status. •We provide for the first time a reference range for S1P in healthy individuals.•The reference range in serum is 0.534–1.242μmol/L (2.5th; 97.5th percentile).•Serum levels of S1P do neither depend on gender nor on age.•The reference range may enable individual cardiovascular risk progression.